CCS VPS (virtual private storage) of La Salle University, Ozamiz City - Bonachita, Leslyn E.; Ogdol, Joseph Meynard; Reazol, Jay Harold S. (2011)
The File Handling System of the Computer Laboratories of the Computer Laboratories of the College of Computer Studies in La Salle University, Ozamiz City has not been using any advanced file handling systems. Respondents were the students who enrolled in a computer subject and the 11 CCS Faculty members. Findings revealed that the students and faculty members who have been using different computers encountered several problems such as loss of documents, corrupted files, widespread of computer viruses and unsecured files that lead to the copied exercises. Because of these, most often, delays in doing computer exercises and the reliabiliy of the created files occur. Thus, this descriptive research design was conducted which aimed at developing the file handling system that helps at minimizing if not eliminating such existing problems.
Keywords: File systems (Computer Science); File management (Computer science)